Urgensi Constitutional Complaint dalam Melindungi Hak Konstitusional Warga Negara - Riskiyawan Hasan (UIN Sunan Kalijaga Yogyakarta, 2023)
Violations of the constitutional rights of citizens from state institutions & public bureaucratic institutions must be the most important focus for a country that places law above and becomes the principle that regulates the administration of the state. In Indonesia, violations of the constitutional rights of citizens are still often carried out by the nation. But until now there is no legal instrument that can be used to obtain justice for violations of these rights. The argument of this study is an effort to provide an overview of the importance of constitutional legal efforts as a form of protection of citizens' rights based on the provisions contained in the 1945 Constitution. This study uses a legal-normative approach, namely research carried out based on the main legal material by examining theories, principles, legal principles & statutory regulations related to this study. The focus of this article is; first, the urgency of constitutional complaints in Indonesia, as well as constitutional complaints as a form of protection of the constitutional rights of every citizen. Abstrak: Pelanggaran terhadap hak konstitusional warga negara dari lembaga negara maupun kelembagaan birokrasi publik harus dijadikan sorotan terpenting untuk negara yang menempatkan hukum sebagai dasar dan menjadi asas yang mengatur penyelenggaraan negara. Di Indonesia, pelanggaran terhadap hak konstitusional warga negara masih sering terjadi dalam praktek kebangsaan. Tetapi hingga sekarang ini tidak terdapat instrumen hukum yang bisa digunakan untuk memperoleh keadilan atas pelanggaran hak tersebut. Argumentasi dari tulisan ini sebagai upaya untuk memberikan gambaran tentang pentingnya upaya hukum konstitusional selaku bentuk perlindungan hak warga negara berdasarkan peraturan yang tercantum pada UUD 1945. Pada kajian ini memakai penelitian hukum- normatif, yakni pendekatan yang dilaksanakan berlandaskan bahan hukum utama melalui metode meneliti teori, prinsip, asas hukum maupun aturan undang-undang yang berkaitan dengan kajian ini. Fokus kajian ini adalah; pertama, urgensi constitutional complaint khususnya Indonesia, serta pengaduan constitutional complaint selaku wujud perlindungan hak konstitusional setiap warga negara